A new approach to the Scoreboard. Issue 4 (14th September 2015) - Magazzino, Cosimo; Felici, Francesco; Bozic, Vanja
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the information content of the variables that can help detecting external and internal imbalances in an early stage. The starting point is the Scoreboard, where nine indicators are chosen in order to increase macroeconomic surveillance of all member states. Design/methodology/approach – This paper provides an overview of the variables that could be informative for imbalances by focusing on EU-27 countries over the period 1960-2010. The number of chosen variables is 28, and they are aggregated in six macro-areas. Therefore, once an imbalance is observed in any of those areas, it is possible to detect in a simple way which specific variable is determining such outcome. Findings – In general, this approach provides reliable signal to the policy-makers about the indicators that can drive imbalances within the area, shedding light on the relationship among the variables included in the analysis, too. Research limitations/implications – In fact, the empirical results underline some well-known critical issue for several countries, and is largely in line with results obtained in a variety of EC and OECD studies. Originality/value – The main added value of the approach adopted in this paper is the introduction of more variables than those initially proposed by the European Commission in the construction of the Scoreboard. This provides more information about the macroeconomic situation in each country, preserving, however, the simplicity of the analysis as the variables are aggregated by homogeneous areas.